Telaah Kitab Mukhtārul Aḥādīts Karya Moenawar Chalil: Studi Kitab Hadis Nusantara - Hasyim, Muhammad Sulaiman; Fauziah, Malihatul; Muhid, Muhid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This paper aims to examine in depth and examine the book Mukhtārul Aḥādīts by a Nusantara scholar named Moenawar Chalil who is famous as one of the leaders of Masyumi (Majlis Syura Muslimin Indonesia). In this research, the author uses a library research method by referring to the main work of Moenawar Chalil, namely the book Mukhtarul Aḥādīts which is a collection of selected hadiths based on discussions of fiqh. The results of this study indicate that the book Mukhtārul Aḥādīts is a book of hadith in Indonesian that broadly discusses fiqh issues where each chapter contains several hadiths along with complete explanations as well as opinions from fiqh scholars, especially the Aṣhāb al-Madzāhib (Imam Madzhab). The Mukhtārul Aḥādīts book also has its own methods and systematics that make it appear different from other Nusantara hadith books. For example, cutting the sanad to the companions' rāwi but still being able to mention problematic rāwis in the sanad. The existence of this book is also one of the treasures of real evidence of the development of hadith books in the Nusantara, especially in the 20th century. Although this book still has several shortcomings and is currently very rare or even no longer studied, because this book is very rare and quite difficult to obtain.